Ecomallow / Intan Darlina Mohammad Khalid ...[et al.] - Mohammad Khalid, Intan Darlina; Muzafar, Marissa; Ishtiaq Ahmad, Mahnoor Shahirah; Khalid, Kharis (2023)
In summary, EcoMallow is a partnership business venture between 4 business partnership. The signature product produced by EcoMallow are EcoMallow Pop which are ready-made and able to be purchased in-store and Ecomallow Bouquet which are made upon custom request. With only two main products, EcoMallow can be labeled as a specialised store for chocolate coated marshmallow products. EcoMallow has surveyed and located the best area to open a physical shop to further put our presence in public and attracting potential customers. The location was determined to be at Fortuna Business Hub addressed at Jalan Lembah 19, Masai, Pasir Gudang, Johor. The location was chosen based on factors such as near universities and residential areas, well established place of business, close proximity to suppliers, store is facing the main road, accessibility, and price of rental space. Due to the advantageous location, the marketing strategy is observed to be easier as the store would be facing the main road where curious customers may come by. To further our audience, EcoMallow will be on social media platforms (i.e Facebook, TikTok, Instagram). Additionally, promotional discount and deals are offered to retain the loyalty of customers. Based on the financial plan, EcoMallow business venture was proven to be a great venture to continue with as no significant loss can be seen from the planning. As years pass, EcoMallow would be a thriving business as its name is spread and known to the public; therefore an increase in production and sales. Profits are proven to increase as years go by for at least the next two consecutive years. As years pass, EcoMallow would be a thriving business as its name is spread and known to the public; therefore an increase in production and sales. To sum up, the finest initiative to provide the community with the best service that we have to offer is EcoMallow. As mentioned before in our vision, to be known as the "sweetest" sensation in town and become the go-to place for specialized gifts and snacks for those with a little sweet tooth. We think that having a sweets shop adjacent to a residential area can elevate the loving lifestyle status in the neighborhood. Therefore, since our activity significant influence on the community, we must obtain consent before we can begin. Last but not least, finishing this ENT300 business plan has provided us with the ideal opportunity to learn how to start our own firm. Therefore, ENT300 is crucial for us since it will inform and inspire us to found our own new company so that we can survive in the future.